Awareness, Attitudes, and Practices of Infection Control in Libya: A Mixed-Methods Study - Atia, Ahmed; Dardar, Orjwan; Shambi, Yameen; Mahdi, Abeer El; Belgasm, Hafsa (Journal of Pharmacy Practice and Community Medicine, 2026)
Infection Prevention and Control (IPC) is essential for reducing healthcare-associated infections, yet gaps between awareness and practice persist, particularly in resource-limited settings. This study was conducted to evaluate awareness, attitudes, and practices related to infection control among healthcare workers, medical students, and the public in Libya. A mixed-methods design was employed, combining a structured, self-administered questionnaire with direct observational assessments in hospitals, clinics, and community settings. The questionnaire included demographic, closed-ended, and open-ended items addressing hand hygiene, Personal Protective Equipment (PPE) use, and environmental cleaning. A pilot study refined the tool before full distribution. Quantitative data were analyzed using Microsoft® Excel, while qualitative responses were thematically analyzed. Of 150 participants, 86.7% reported knowing the meaning of infection control, though only 63.3% had received formal training. High awareness of hand hygiene and PPE use was observed, yet compliance challenges and institutional trust deficits were evident. Observational data confirmed lapses in practice, particularly in clinical settings. While awareness of IPC measures is high, consistent practice remains limited. Expanding structured training, embedding IPC education in schools, and strengthening institutional accountability are critical to bridging the gap between knowledge and behavior.
Keywords: Infection control; Hand hygiene; Personal protective equipment; Healthcare-associated infections; Libya